Resource allocation in university libraries - Devarajan, G. (New Delhi : Ess Ess Publications, 1993)
Study with reference to Kerala.
Includes bibliographical references.
Includes index.
Keywords: Academic libraries -- Finance -- India -- Kerala; Academic libraries -- Administration -- India -- Kerala